Papular Acne Scars of the Nose and Chin: An Under-recognised Variant of Acne Scarring - Ali, Faisal R (J Cutan Aesthet Surg, 2016)
BACKGROUND: Scarring following acne vulgaris is common and can be of profound psychosocial consequence. AIMS AND OBJECTIVES: We have clinically noted a variant of acne scarring, overlooked by previous categorisation schemes, which we have denominated as papular acne scars of the nose and chin. We sought to characterise these novel entities further. MATERIALS AND METHODS: Initially, we identified 14 patients with papular acne scars of the nose and chin in a cosmetic dermatology clinic, of whom two were female and rest were male. We then prospectively evaluated 100 consecutive patients attending our tertiary referral acne isotretinoin clinic and 49 patients attending a general dermatology clinic. RESULTS: Amongst 149 patients, from a general dermatology and tertiary acne clinic, soft papular scars were noted in four patients, distributed on the nose and chin. Three of the four patients were male, three patients had additional acne scars and the median age was 23.5. CONCLUSIONS: We have identified 18 patients with papular acne scars of the nose and chin and propose that this new category should be added to acne scarring classification schemes. Future work should be directed at corroborating the epidemiology of such lesions and describing effective treatment modalities.